2011
DOI: 10.1186/1743-7075-8-54
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a ketogenic diet on the quality of life in 16 patients with advanced cancer: A pilot trial

Abstract: BackgroundTumor patients exhibit an increased peripheral demand of fatty acids and protein. Contrarily, tumors utilize glucose as their main source of energy supply. Thus, a diet supplying the cancer patient with sufficient fat and protein for his demands while restricting the carbohydrates (CHO) tumors thrive on, could be a helpful strategy in improving the patients' situation. A ketogenic diet (KD) fulfills these requirements. Therefore, we performed a pilot study to investigate the feasibility of a KD and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
223
0
11

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(241 citation statements)
references
References 45 publications
(62 reference statements)
7
223
0
11
Order By: Relevance
“…These diets have not only led to weight loss without direct calorie restriction they have resulted in improvement in the risk factors associated with CVD when animal and other fats are used (Foster et al 2003;Volek et al 2003;Herron et al 2004;Sharman and Volek 2004;Volek and Sharman 2004;Yancy et al 2004Yancy et al , 2010Brinkworth et al 2009;Sacks et al 2009). Moreover, trials of ketogenic diets in the treatment of final stage cancer patients and in experimental systems (Tisdale et al 1987;Breitkreutz et al 2005;Zuccoli et al 2010;Ho et al 2011;Klement and Kaemmerer 2011;Schmidt et al 2011;Chang et al 2013) have occurred, with some interesting results of reduction in tumour size, reduction of cachexia, or delay of initiation of cancer. Ketogenic diets continue to be used to treat some classes of epilepsy (Freeman et al 1998;Kossoff et al 2006;Neal et al 2008), and have been suggested for other mental disorders or dementias including Alzheimer's disease and Parkinson's disease (VanItallie and Nufert 2003;Kim et al 2007;Kossoff and Hartman 2012).…”
Section: Health Effects Of Fat As a Macronutrient And Energy Sourcementioning
confidence: 99%
“…These diets have not only led to weight loss without direct calorie restriction they have resulted in improvement in the risk factors associated with CVD when animal and other fats are used (Foster et al 2003;Volek et al 2003;Herron et al 2004;Sharman and Volek 2004;Volek and Sharman 2004;Yancy et al 2004Yancy et al , 2010Brinkworth et al 2009;Sacks et al 2009). Moreover, trials of ketogenic diets in the treatment of final stage cancer patients and in experimental systems (Tisdale et al 1987;Breitkreutz et al 2005;Zuccoli et al 2010;Ho et al 2011;Klement and Kaemmerer 2011;Schmidt et al 2011;Chang et al 2013) have occurred, with some interesting results of reduction in tumour size, reduction of cachexia, or delay of initiation of cancer. Ketogenic diets continue to be used to treat some classes of epilepsy (Freeman et al 1998;Kossoff et al 2006;Neal et al 2008), and have been suggested for other mental disorders or dementias including Alzheimer's disease and Parkinson's disease (VanItallie and Nufert 2003;Kim et al 2007;Kossoff and Hartman 2012).…”
Section: Health Effects Of Fat As a Macronutrient And Energy Sourcementioning
confidence: 99%
“…Patients' self-reported quality of life and psychosocial status will likely improve if adipose tissue mass loss (and skeletal muscle, as well) was dampened -in part because patients may feel that they are in better control of their weight and can keep their strength, and also in part because conservation of adipose tissue mass would likely result in a decrease in anti-tumor therapy toxicities. While studies investigating a ketogenic diet demonstrate improved quality of life in patients with advanced cancer, 98 to our current knowledge, no studies have investigated the capability to restore adipose tissue mass and the subsequent effect of restoring adipose tissue mass on CAC. A comprehensive understanding of the physiology and pathophysiology of adipose tissue, cancer, and CAC will hopefully lead to the discovery of key components and drivers within the development and progression of CAC that can be manipulated and targeted to benefit the patient.…”
mentioning
confidence: 99%
“…Tumor cell lines of colon, breast, gastric and prostate cancer, and both animal and human cancer subjects showed tumor stability or shrinkage on low carbohydrate diets or conditions of low glucose/ glutamine [7][8][9][10][11]. In-vitro exposure of tumor cells to glycolytic inhibitors also decreased cell proliferation and survival, as well as increased cell necrosis [12][13][14].…”
Section: Previous Studiesmentioning
confidence: 99%
“…The ketogenic diet has been in use for decades in the treatment of refractory epilepsy for which it appears to be safe as well as very effective. A previous pilot study showed tolerability of a similar diet in 10 human cancer subjects for up to 4 weeks, while another study involving 16 patients showed 5 patients completing up to 12 weeks on the diet [7,8].…”
Section: Introductionmentioning
confidence: 99%